An X‐band compact and low‐profile waveguide magic‐T. Issue 9 (21st May 2019) - Vincenti Gatti, Roberto; Rossi, Riccardo; Dionigi, Marco; Spigarelli, Alessandro
Abstract: An X‐band low‐profile waveguide magic‐T is presented as a combination of two compact and co‐planar E‐plane and H‐plane T‐junctions. Two architectures are proposed according to the sum and difference ports lying on the same side or on opposite sides. This can be an attractive feature in the design of compact architectures. A proof of concept is manufactured with low‐cost 3D printing technology and electroplated. Good agreement between simulated and measured results is observed.